Genocide and resistance Nr. 12(2) - Starkauskas, Juozas; Jonušauskas, Laurynas; Streikus, Arūnas; Jaseliūnas, Egidijus; Bubnys, Arūnas; Brandišauskas, Valentinas; Liekis, Šarūnas; Gailienė, Danutė; Domanskaitė-Gota, Vėjūnė; Kazlauskas, Evaldas; Landsbergis , Vytautas; Zingeris, Markas; et al. (Genocidas ir rezistencija, 2002)
Full Issue (paper copy scan)